Maternal Religiosity, Family Resources and Stressors, and Parent–Child Attachment Security in Northern Ireland - Goeke-Morey, Marcie C. (Soc Dev, 2012)
This study explores the associations between mothers' religiosity, and families' and children's functioning in a stratified random sample of 695 Catholic and Protestant mother-child dyads in socially deprived areas in Belfast, Northern Ireland, a region which has experienced centuries of sectarian conflict between Protestant Unionists and Catholics Nationalists. Findings based on mother and child surveys indicated that even in this context of historical political violence associated with religious affiliation, mothers' religiosity played a consistently positive role, including associations with multiple indicators of better family functioning (i.e., more cohesion and behavioral control and less conflict, psychological distress, and adjustment problems) and greater parent-child attachment security. Mothers' religiosity also moderated the association between parent-child attachment security and family resources and family stressors, enhancing positive effects of cohesion and mother behavioral control on mother-child attachment security, and providing protection against risks associated with mothers' psychological distress. Findings are discussed in terms of implications for understanding the role of religiosity in serving as a protective or risk factor for children and families.